Synthesis, characterization and pharmacological evaluation of pyrazolyl urea derivatives as potential anti-inflammatory agents - Kanagasabai Somakala; Mohammad Amir (Elsevier, 2017)
p38α mitogen activated protein kinase (MAPK) inhibitors provide a novel approach for the treatment of inflammatory disorders. A series of fifteen pyrazolyl urea derivatives (3ao) were synthesized and evaluated for their p38α MAPK inhibition and antioxidant potential. Compounds 3ae, 3g and 3h showed low micromolar range potency (IC50 values ranging from 0.037 ± 1.56 to 0.069 ± 0.07 µmol/L) compared to the standard inhibitor SB 203580 (IC50 = 0.043 ± 3.62 µmol/L) when evaluated for p38α MAPK inhibition by an immunosorbent-based assay. Antioxidant activity was measured by a 2,2'-diphenyl-1-picryl hydrazyl radical (DPPH) free radical scavenging method and one of the compounds, 3c, showed better percentage antioxidant activity (75.06%) compared to butylated hydroxy anisole (71.53%) at 1 mmol/L concentration. Compounds 3ae, 3g and 3h showed promising in vivo anti-inflammatory activity (ranging from 62.25% to 80.93%) in comparison to diclofenac sodium (81.62%). The ulcerogenic liability and lipid peroxidation activity of these compounds were observed to be less in comparison to diclofenac sodium. These compounds also potently inhibited the lipopolysaccharide (LPS)-induced TNF-α release in mice (ID50 of 3ac = 19.98, 11.32 and 9.67 mg/kg, respectively). Among the screened compounds, derivative 3c was found to be the most potent and its binding mode within the p38α MAPK is also reported.